Can Interventions Spur Development of the Insurance Sector? : From Examples of World Bank Projects - World Bank (World Bank, Washington, DC, 2020)
Section one of the paper provides a broad overview of the nature and objectives of the projects. Section two contains an objective view of the impact of FIRST funded projects on the growth in insurance markets as measured by insurance market penetration. Rigorous data analysis was used to isolate exogenous factors other than the project intervention that may have led to a change in the insurance premiums as a percentage of GDP. The paper showcases in section three, the dynamic view and multipronged approaches to the insurance market development by highlighting country case studies, with different primary objectives, towards the overall goal of the insurance market development. The case studies also consider the specific insurance market interventions that can stimulate wider financial sector development objectives. Applying the drivers and stages discussion as an analytical framework, section four takes stock of numerous interventions of the FIRST projects implemented by the World Bank and extracts some key lessons learned that could be used as a guide to inform the design of future intervention, and by policy makers in pursuit of insurance market development. Finally, section five provides some overarching conclusions and takeaways.